2022
DOI: 10.3390/w14030491
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Permeable Clay Brick Pavement for Pollutant Removal from Varying Strength Stormwaters in Arid Regions

Abstract: Permeable pavement is a low impact development technology for stormwater (SW) runoff control and pollutant removal. The strength of SW depends on land use of the catchment, e.g., semi-urban vs. industrial. The performance (in terms of pollutants removal) of permeable clay bricks (PCB) has not been adequately assessed for SW of varying strengths. For using the permeable clay bricks as a pavement surface layer, the present research investigates its pollutant removal capacity through SW infiltration using a labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A modified PPS with grass swale can correspondingly reduce TSS, NO 3 -N, NH 3 -N, and TN up to 91%, 66%, 85%, and 42%, whereas heavy metals such as Cu, Fe, Pb, Mn, and Zn can be reduced by more than 75% [17]. A recent study by Shafiquzzaman et al [18] reported that a PPS surface made of permeable clay bricks could reduce up to 99% TSS, 65-70% organics (BOD and COD), 70% NH 3 -N, and 94% Pb from polluted stormwater.…”
Section: Introductionmentioning
confidence: 95%
“…A modified PPS with grass swale can correspondingly reduce TSS, NO 3 -N, NH 3 -N, and TN up to 91%, 66%, 85%, and 42%, whereas heavy metals such as Cu, Fe, Pb, Mn, and Zn can be reduced by more than 75% [17]. A recent study by Shafiquzzaman et al [18] reported that a PPS surface made of permeable clay bricks could reduce up to 99% TSS, 65-70% organics (BOD and COD), 70% NH 3 -N, and 94% Pb from polluted stormwater.…”
Section: Introductionmentioning
confidence: 95%